Business database systems - Connolly, Thomas (Addison-Wesley, 2008)
"Databases are the underlying framework of any information system. As such, the fortunes of any business or organisation, in no small way, rest upon the efficacy and efficiency of their database systems. Business Database Systems arms you with the knowledge to analyse, design and implement effective, robust and successful databases. Using a tried and tested three-phase methodology, the authors lucidly describe each facet of the database development lifecycle, giving you a complete understanding of the fundamentals in this key topic area and helping you to ensure that your databases are the best that they possibly can be." "This book is ideal for students of Business/Management Information Systems, or Computer Science, who will be expected to take a course in database systems for their degree programme. It is also suited to any practitioner who needs to learn, or refresh their knowledge of, the essentials of database management systems."--Jacket